Influence of Organizational Culture and Leadership on Employee Performance through Motivation as an intervening variable in PT. PLN ( Persero ) Semarang Area - Setiawan, Yanuar Aditya; Pradhanawati, Ari; Budiatmo, Agung (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
PT. PLN ( Persero ) area of Semarang is a company engaged in the provision of electricity services in Semarang. This study aims to determine themselves the extent of the influence of organizational culture ( X1 ) , Leadership ( X2 ) , Motivation ( Z ) of the Employee Performance ( Y ) PT. PLN ( Persero ) Semarang area . This type of research is explanatory research , the method of data collection using oral interviews and data collection devices using a questionnaire with a sample of 91 respondents employees of PT PLN ( Persero ) Semarang area through sampling techniques performed by sampling saturated or also known as the census . Results from this study is that there is influence between organizational culture , leadership , and motivation on employee performance PT. PLN ( Persero ) Semarang area of 60.6 % , while 39.4 % is influenced by other factors . Then the most impact is affecting the performance of organizational culture indirectly ( indirect ) through the motivation of 0.088 . Compared with the leadership to influence performance indirectly ( indirect ) amounted to 0,089 . This means that the organizational culture and leadership will not be able to affect the performance , if the employee has previously had the motivation of organizational culture and leadership are given .. Advice can be given in this study , namely PT . PLN ( Persero ) Semarang area is to create a climate of better organizational culture within the company , it should be held periodically evaluate the implementation of Electricity for a Better Life.